How Turkish is it? Art and culture in Vienna - Sievers, Wiebke (Migration Letters, 2014)
<span style="font-family: ’Bookman Old Style’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB; mso-bidi-language: AR-SA;" lang="EN-GB">The Viennese Turkish community constitutes 4% of all people residing in Vienna. This considerable presence has also brought with it many artistic and cultural activities. In this paper I question how far these activities have diversified Viennese cultural life. The results are two-fold: my quantitative analysis of public-funding data shows that Viennese Turkish artistic activities are still perceived as a marginal addendum to Viennese cultural life. However, as my qualitative analysis of selected activities highlights, they have contributed to making the diversity of both Austrian and Turkish cultures visible, albeit only in the margins, rather than in the center of Viennese cultural life.